2015
DOI: 10.3748/wjg.v21.i30.9002
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer and Fournier’s gangrene - current knowledge and therapeutic options

Abstract: Fournier's gangrene (FG) is a rapid progressive bacterial infection that involves the subcutaneous fascia and part of the deep fascia but spares the muscle in the scrotal, perianal and perineal region. The incidence has increased dramatically, while the reported incidence of rectal cancer-induced FG is unknown but is extremely low. Pathophysiology and clinical presentation of rectal cancer-induced FG per se does not differ from the other causes. Only rectal cancer-specific symptoms before presentation can lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 148 publications
1
32
1
1
Order By: Relevance
“…There were 23 cases evaluated in a review by Bruketa et al [2]; in Japan, 17 cases including the present case have been reported (Table 1). The median age in the Japanese group was 58 (range, 30–80) years with a male to female ratio of 15:2.…”
Section: Discussionmentioning
confidence: 93%
“…There were 23 cases evaluated in a review by Bruketa et al [2]; in Japan, 17 cases including the present case have been reported (Table 1). The median age in the Japanese group was 58 (range, 30–80) years with a male to female ratio of 15:2.…”
Section: Discussionmentioning
confidence: 93%
“…[68] In addition, colon cancer can induce Fournier gangrene. [9,10] Therefore, the urinary tract can be affected by direct tumor invasion or tumor-associated inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Colorectal cancer also can induce the same inflammatory process and fistula formation. Bruketa et al [9] ever concluded that the perforated rectal cancer could induce Fournier gangrene with perineum fascia extension and absence of testis involvement. However our case presented as annular rectal cancer with prostate invasion, which hypothesized to process the development of emphysematous epididymo-orchitis through the vas deferens via backflow of gas-producing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotising fasciitis of the perineum is a rare presentation of advanced rectal cancer 14. Since necrotising fasciitis is more common in elderly and immunocompromised patients, and carries high mortality,4 7 and because rectal cancer is usually in the perforated stage, aggressive curative-intent therapy is often not possible 9 13 15.…”
Section: Discussionmentioning
confidence: 99%